Vegetation of quartz fields in the Little Karoo, Tanqua Karoo and eastern Overberg (Western Cape Province, South Africa) - Mucina, Ladislav; Schmiedel, U. (2006)
Quartz fields are a very special habitat characterised by occurrence of pavements of angular quartz debris being the result of weathering of quartz veins embedded in soft bedrock (shale, phyllite). Quartz fields support vegetation dominated by leafsucculent dwarf shrubs, belonging to the Aizoaceae (mainly subfamilies Mesembryanthemoideae and Ruschioideae), Crassulaceae and Asteraceae. In this study we have described and classified plant communities of the quartz fields of the Little Karoo and adjacent regions (Tanqua Karoo, Overberg) in the Western Cape Province (South Africa). Here we present data and ideas on species composition, life-form texture, physiognomic structure, species richness, habitat preferences, geographic distribution, and conservation status ofthe quartz fields and their constituent plant species. Locally endemic taxa of the genus Gibbaeum (Haw.) N. E. Br. (Aizoaceae) are dominating most of the studied quartz fields. This paper features sixteen plant communities, all of them formally described as new associations and all of them, except for the Drosanthemo-Psilocauletum juncei, largely limited to quartz field habitats. They are classified into 5 community groups, of which the Gibbaeion angulipedis, Gibbaeo dispar-Lampranthylion altistyli and Gibbaeo nuciformi-Pteronion viscosi are being formally recognized as alliances. This paper is a pioneering attempt to present a first formal syntaxonomy of the vegetation of a region of the Succulent Karoo Biome in South Africa.